The Effect of Perceived Organizational Support On Organizational Citizenship Behavior Through Organizational Commitment & Organizational Justice as Mediation Variables - Diaz Ayu Fardianasari; Arief Purwanto; Nasharuddin Mas (Optima Science, 2025)
The purpose of this study wa to determine the effect of perceived organizational support on organizational citizenship behavior with organizational commitment as a mediating variable (Study at Btari Agency Malang City). The population in this study were all staf, both general and operational staff at Btari Agency Malang. The sampling technique in this study used